2013
DOI: 10.1111/jvim.12130
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastographic Evaluation of Dogs with Congenital Portosystemic Shunts

Abstract: Background: On plasma-based assays, dogs with congenital portosystemic shunts (CPSS) have changes in serum concentrations of both pro-and anticoagulant proteins, but how these abnormalities affect whole blood coagulation assays (eg, thromboelastography) are unknown.Objectives: To conduct kaolin-activated thromboelastography (TEG) analysis in dogs with CPSS and to compare TEG coagulation status with clinical presentation, routine serum biochemistry, and plasma-based coagulation tests.Animals: Twenty-one client-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 15 publications
2
41
0
3
Order By: Relevance
“…After a 30‐minute hold period at room temperature, a single operator performed kaolin‐activated TEG. Reference ranges for TEG variables were established in the Coagulation Laboratory in the Foster Hospital at the Cummings School . The remaining citrated plasma was stored at −80°C for analysis of PT, , aPTT, , quantitative fibrinogen, , AT activity, , PC activity, , d‐dimers, , and vWF activity , .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a 30‐minute hold period at room temperature, a single operator performed kaolin‐activated TEG. Reference ranges for TEG variables were established in the Coagulation Laboratory in the Foster Hospital at the Cummings School . The remaining citrated plasma was stored at −80°C for analysis of PT, , aPTT, , quantitative fibrinogen, , AT activity, , PC activity, , d‐dimers, , and vWF activity , .…”
Section: Methodsmentioning
confidence: 99%
“…Similar to humans with cholestasis, dogs with extrahepatic bile duct obstruction most often are hypercoagulable . In addition, dogs with portosystemic shunts appear to be mildly hypercoagulable . No studies to date have reported TEG findings in dogs with ALD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, the value of TEG in predicting coagulation status in dogs with CH is unknown. Plasma fibrinogen concentrations seemingly reflect TEG indices of clot strength in dogs with liver disease . As such, plasma fibrinogen concentration is recommended for bleeding risk assessment in CH …”
Section: Biopsy Acquisitionmentioning
confidence: 99%
“…Most studies assessing coagulation in dogs with a CPSS or other hepatic disease have investigated for the presence of hypocoagulability, [1][2][3][4] and one study has identified hypercoagulability in some dogs with a CPSS. 5 Previous studies of dogs with CPSS have shown that 35-84% had microcytosis and 16-70% were anaemic, whilst 7-53% had a prolonged prothrombin time, and 5-64% had a prolonged activated partial thromboplastin time (aPTT). 1,[3][4][5][6][7][8][9][10] A leukocytosis is variably present with documented prevalence of between 15.4-40%.…”
Section: Introductionmentioning
confidence: 99%